(untitled) (Historia, 2021)
Apartheid as a system of government as practised in twentieth-century South Africa is well known globally: an account of the complex legal nature of the system is an area few have been able to explain, however. An international law scholar and advocate for human rights, John Dugard’s contribution in the struggle against apartheid was to challenge the legal features of apartheid. He was “involved in the dispute over the legal status of South West Africa and later as United Nations special rapporteur on human rights in occupied Palestine” (p 3). Derived from the author’s personal participation in the three cases discussed in this book, Confronting Apartheid provides an account of “apartheid, or a system akin to it” and his experiences “in opposition to it in both South Africa and South West Africa”. He goes on to explain that he was “fully exposed to Israel’s practices as the occupying power of Palestine” (p 3).